A microstrip sensor for determination of harvesting time for oil palm fruits (Tenera: Elaeis guineensis) - Khalid, K.; Abbas, Z. (Taylor and Francis Group, 1992)
This paper deals with the application of a microstrip sensor in setting up a harvesting system with the objective of obtaining the optimum oil yield and oil quality in the fruits. The moisture content in the fresh mesocarp of the outer fruit of the bunch and corresponding magnitude of insertion loss (|S21|) of a microstrip sensor were monitored at weekly intervals from 12 weeks after anthesis until the fruits were fully ripe and harvested. A close relationship between moisture content and oil content in mesocarp has been found. The sensor not only provided an objective measure for harvesting but also proved suitable for assessing the quality of fruits that reach the processing plant.